Impact of Network Finance Development on Inflation: Evidence from Chinese Market - Junwen, Feng; Gang, Wang; Yuchen, Wu (The Economics and Finance Letters, 2019)
With the rapid development of computer, communications, Internet and database technology, the society entered the era of the Internet economy. At present, as the impacts on the development of network finance, the three elements of technology, economic and social are in rapid change and development, at the same time, the financial network has also been considerable development, a variety of online banking, so-and-so Bao everywhere, P2P net loan platform as sprung up in public view. The flourishing financial network has attracted a lot of money from reality to the network platform, the currency in circulation had seen a considerable impact, as a monetary phenomenon whether this change will have an impact on inflation, this article is to discuss the problem. This article from the perspective of a qualitative and quantitative study of the network of financial development of inflation, respectively, will eventually make some recommendations lying on the conclusions of this paper to the monetary policy under the influence of the inflationary effects.